The philosophy of science a contemporary introduction - Rosenberg, Alexander 1946-; McIntyre, Lee C. (New York Routledge, Taylor & Francis Group, 2020)
"Any serious student attempting to better understand the nature, methods, and justification of science will value Alex Rosenberg's and Lee McIntyre's updated and substantially revised Fourth Edition of Philosophy of Science: A Contemporary Introduction. Weaving lucid explanations with clear analyses, the volume is as a much-used, thematically-oriented introduction to the field"--
The relationship between philosophy and science -- Why is philosophy of science important? -- Scientific explanation -- Why do laws explain? -- Causation, inexact laws, and statistical probabilities -- Laws and explanations in biology and the "special sciences" -- The structure of scientific theories -- Epistemic and metaphysical issues about scientific theories -- Theory construction vs. model building -- Induction and probability -- Confirmation, falsification, underdetermination -- Challenges from the history of science -- Naturalism in the philosophy of science -- The contested character of science -- Science, relativism, and objectivity.
Includes bibliographical references and index.
Keywords: Science -- Philosophy